Prevalence of Osteoporosis and Osteopenia Among Cancer Patients and Associated Risk Factors: A Retrospective Analysis at Najran Cancer Center, Saudi Arabia - Badheeb, Ahmed; Al Sulieman, Mohamed; Ahmed, Faisal; Asiri, Ahmed; Badheeb, Mohamed (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Recent clinical guidelines recommend assessing bone mineral density (BMD) in patients at increased risk for significant bone loss, such as cancer patients. This study aimed to report the prevalence of osteoporosis and osteopenia and their associated factors in cancer patients at Najran Cancer Center, Saudi Arabia. Materials and Methods: This retrospective cross-sectional study was conducted from February 2021 to March 2022, including 39 adult cancer patients receiving treatment at King Khalid Hospital Cancer Center in Najran, Saudi Arabia. Participants were interviewed, and their BMD was assessed using dual-energy X-ray absorptiometry (DXA) scans of the lumbar spine and femoral neck. Univariate analysis was performed to examine the association between osteoporosis and osteopenia and other variables. Results: The study involved 39 adult cancer patients in Najran, Saudi Arabia, with a mean age of 60.15 ± 12.26 years. The majority of patients (53.8%) were aged between 60 and 69 years, and most (64.1%) were female. The primary diagnosis was mostly breast cancer (35.9%) followed by prostate cancer (25.6%). Sixty-six point seven percent (66.7%) of patients received chemotherapy, and 64.1% received hormone therapy. Results showed osteopenia, osteoporosis, and normal BMD in 7 (17.9%), 28 (71.8%), and 4 (10.3%) patients, respectively. Forty-three point six percent (43.6%) had low serum vitamin D levels. While no significant relationship was found between osteopenia/osteoporosis and various factors, it was more frequent in older patients, those undergoing chemotherapy, and those with low vitamin D levels (p = 0.04, 0.05, 0.005, respectively). Conclusion: A higher prevalence of osteoporosis and osteopenia was observed in cancer patients undergoing chemotherapy, older patients, and those with low vitamin D levels. Further research is necessary to determine the most effective strategies for minimizing bone loss in this population.